2020
DOI: 10.1002/ldr.3824
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus additions accelerate decomposition of slow carbon pool and lower total soil organic carbon pool in alpine meadows

Abstract: Nitrogen (N) and phosphorus (P) additions reduced soil organic carbon (SOC) contents and stocks in alpine meadows on the Tibetan Plateau. However, little is known about microbial mechanisms behind SOC decline. This study investigated the effects of long‐term N and P additions on microbial community composition and SOC decomposition (C mineralization (Cm), mean resistant times for active C pool (MRTa), and slow C pool (MRTs) in alpine meadows. Results showed that the total SOC pool was reduced by 2–9% under N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
(192 reference statements)
2
22
0
Order By: Relevance
“…As shown previously, short-term N addition increased the richness and Shannon and McIntosh indices of bacterial and fungal communities in the paddy soil [22]. However, long-term N addition decreased bacterial richness by changing soil pH and plant composition in temperate steppe grassland and increased fungal diversity and relative abundance of complex carbohydrate-decomposing bacterial and fungal groups in alpine meadows [23]. Biogeochemical processes and ecosystem functions are directly associated with altered abundance, diversity, and composition of soil microbial communities [18,24].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…As shown previously, short-term N addition increased the richness and Shannon and McIntosh indices of bacterial and fungal communities in the paddy soil [22]. However, long-term N addition decreased bacterial richness by changing soil pH and plant composition in temperate steppe grassland and increased fungal diversity and relative abundance of complex carbohydrate-decomposing bacterial and fungal groups in alpine meadows [23]. Biogeochemical processes and ecosystem functions are directly associated with altered abundance, diversity, and composition of soil microbial communities [18,24].…”
Section: Introductionsupporting
confidence: 72%
“…Fang et al [69] reported that the decrease in DOC concentration in soil was a consequence of changing microbial decomposition and humidification processes. Soil TP content significantly decreased in the N3 treatment due to the increase in absorption and utilization of TP by plants in a high-N environment [28,67], limiting P availability compared to N [23]. The integrated effect of soil organic carbon stimulation resulted in no significant effect on TC in different N addition treatments.…”
Section: Effects Of Soil Chemical Properties On the Soil Microorganisms Under Nitrogen Addition In Permafrost Peatlandmentioning
confidence: 97%
See 1 more Smart Citation
“…The ratio of carbon to nitrogen was higher under the balanced fertilization and low fertilization treatments (Table S5), which contributed to a reduction in the decomposition of crop residue by soil microorganisms and increased the stabilization rate of plant biomass input carbon, thereby improving SOC sequestration (Lu et al, 2011). In addition, N and P enrichment from a high rate of fertilizer application in the long term can accelerate the decomposition of recalcitrant carbon, leading to negative impact on soil carbon sequestration (J. H. Li et al, 2021). This could result in the lower SOC content in conventional fertilization than that in balanced fertilization.…”
Section: Impacts Of Long-term Tillage and Fertilization On Soc Content And Soc Stocksmentioning
confidence: 99%
“…However, the efficacy of mineral fertilization for increasing SOC sequestration has been questioned in recent studies. J. H. Li et al (2021) reported that fertilization with N and/or P increased SOC decomposition and led to a 2%-9% decrease in the SOC stock at the depth of 0-20 cm. The main reason why fertilization increases SOC sequestration is that fertilization promotes crop growth and increases the amount of crop residue returned to the soil (Lu et al, 2011).…”
mentioning
confidence: 99%